Performance Evaluation of Cross Layer Adaptive Multimedia Transmission: The case of Wired Networks - Christos Bouras; Apostolos Gkamas; G Kioumourtzis (13th International Telecommunications Network Strategy and Planning Symposium - NETWORKS 2008, Budapest, Hungary, 2008)
This paper presents the performance evaluation of the wired part of a proposed framework with cross layer adaptation mechanisms, for multimedia transmission over wired and wireless networks. The performance evaluation of the proposed framework is contacted through a number of simulations with the network simulator software (ns2), which has been enhanced in order to support the functionality of the proposed framework. The performance evaluation includes various simulation scenarios in order to investigate the behavior of the proposed framework under different conditions. The proposed framework can support both wired and wireless receivers in one platform in which, cross layer information are used to support the wireless users whereas TCP friendly estimations are used to support the wired users.